Biofouling Control in Cooling Water - T. Reg Bott (International Journal of Chemical Engineering)
An important aspect of environmental engineering is the control of greenhouse gas emissions. Fossil fuel-fired power stations, for instance, represent a substantial contribution to this problem. Unless suitable steps are taken the accumulation of microbial deposits (biofouling) on the cooling water side of the steam condensers can reduce their efficiency and in consequence, the overall efficiency of power production, with an attendant increase in fuel consumption and hence CO2 production. Biofouling control, therefore, is extremely important and can be exercised by chemical or physical techniques or a combination of both. The paper gives some examples of the effectiveness of different approaches to biofouling control.